Rethinking Risk: The Relevance of Condoms and Viral Load in HIV Nondisclosure Prosecutions - Grant, Isabel (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractAn HIV-positive individual who fails to disclose his or her status to a sexual partner may face charges ranging from nuisance to murder for such behaviour, with the most common charges being aggravated assault and aggravated sexual assault. The number of prosecutions in Canada against individuals who fail to disclose their HIV-positive status to their sexual partners has risen over the last ten years. At the same time, scientific advancements in treatment options and our understanding of transmission, condom usage, and viral load are constantly influencing the assessment of the risk that nondisclosure poses to the complainant in any given case.The author reviews the recent case of R. v. Mabior, the first judgment in Canada to criminalize nondisclosure in the context of protected sex. She argues that encouraging condom use is so important, and that the use of condoms reduces the risk of transmission so significantly, that the criminal law should distinguish between protected and unprotected sex in cases of nondisclosure. The author proceeds to critique the trial judge's reliance on viral load as a factor in determining whether nondisclosure poses a significant risk of serious bodily harm under the test established in Cuerrier. The author argues that the accused's viral load, unlike condom use, is not a manageable standard on which to base culpability.